Reduced in-hospital mortality for heart failure with clinical pathways: the results of a cluster randomised controlled trial. Issue 5 (7th October 2009) - Panella, M; Marchisio, S; Demarchi, M L; Manzoli, L; Di Stanislao, F
Abstract : Background: Hospital treatment of heart failure (HF) frequently does not follow published guidelines, potentially contributing to HF high morbidity, mortality and economic cost. The Experimental Prospective Study on the Effectiveness and Efficiency of the Implementation of Clinical Pathways was undertaken to determine how clinical pathways (CP) for hospital treatment of HF affected care variability, guidelines adherence, in-hospital mortality and outcomes at discharge. Methods/design: Two-arm, cluster-randomised trial. Fourteen community hospitals were randomised either to the experimental arm (CP: appropriate therapeutic guidelines use, new organisation and procedures, patient education) or to the control arm (usual care). The main outcome was in-hospital mortality; secondary outcomes were length and appropriateness of the stay, rate of unscheduled readmissions, customer satisfaction, usage of diagnostic and therapeutic procedures during hospital stay and quality indicators at discharge. All outcomes were measured using validated instruments available in literature. Results: In-hospital mortality was 5.6% in the experimental arm (n = 12); 15.4% in controls (n = 33, p = 0.001). In CP and usual care groups, the mean rates of unscheduled readmissions were 7.9% and 13.9%, respectively. Adjusting for age, smoking, New York Heart Association score, hypertension and source of referral, patients in the CP group, as compared to controls, had a significantly lower risk of in-hospital death (OR 0.18; 95% CI 0.07 to 0.46) and unscheduled readmissions (OR 0.42; 95% CI 0.20 to 0.87). No differences were found between CP and control with respect to the appropriateness of the stay, costs and patient's satisfaction. Except for electrocardiography, all recommended diagnostic procedures were used more in the CP group. Similarly, pharmaceuticals use was significantly greater in CP, with the exception of diuretics and anti-platelets agents. Discussion: The introduction of a specifically tailored CP for the hospital treatment of HF was effective in reducing in-hospital mortality and unscheduled readmissions. This study adds to previous knowledge indicating that CP should be used to improve the quality of hospital treatment of HF. Trial registration number: NCT00519038